Effect Misfire Density of colored Oxides ( SnO2 , CoO) In Glaze - Ahmed-Hamza, Samer; Sabah Albakry, Haider; Mohamed Soliman, Monther (Opción, 2019)
In this research a glass mixture is formulated from a group of acidic, basal and neutral compounds according to specific weight ratios to produce a glass that matures at low temperature to be applied to the surface of the clay body. Colored ceramic glass using black cobalt oxide (CoO) at a constant rate of (1%) With the addition of tin oxide with different weight ratios of (1 - 8%) with glass mixture and within the composition to study the effect of this opaque oxide in the nature of surface, color and tangible results of the ceramic body, the burning is done using an electric oven and the temperature (920 m) and maturity time ( One hour ). Where the cobalt oxide works on the coloring of the glass mass to be a colored base through which shows the effect of dark ox- ide ((SnO2) and invest the difference in the coefficient of density and surface tension and the melting point between the cobalt oxide and tin oxide to create liquid darkness within the layer of glass through the property (phase - phase The effect of this characteristic was clearly graded by different ratios. 1- 1-2% did not give clear results due to the melting action of cobalt oxide. 2 - (3 - 4%) color became less intense with the appearance of small color spots on the surface. 3- (5-6%) the appearance of color spots on the surface in large sizes. 4- The percentage of (7 - 8%) clear spread of color spots due to the difference of density and tensile strength with reduced effect of colored oxide